Effect of denture wearing on occurrence of fungal isolates: An original study - Gagandeep K Chahal; Harkanwal P Singh (Wolters Kluwer Medknow Publications, 2024)
The present study aimed to evaluate the effect of denture wearing on the occurrence of fungal isolates in the oral cavity before and after complete denture insertion. Fifty completely edentulous patients were selected. Swab samples were collected intraorally before the fabrication of complete dentures from the palatal mucosal surface and after complete denture fabrication (1 and 7 days after denture insertion). Further, these samples were inoculated and incubated. Results showed that in 48 patients, no isolate of fungus before denture insertion was found. In two subjects, results were false positive (contamination from the environment), and in six patients, there was an increase in growth, but not much significant increase of growth was seen (mild growth of fungus only after denture insertion). One of the major findings of this study was that the overall occurrence of fungal isolates (before and after denture insertion) in the oral cavity was not significant.